Recent Developments in Receptor-Selective Retinoids - Nagpal, S.; Chandraratna, R.A.S. (Current Pharmaceutical Design, 2000)
Natural (all trans-retinoic acid, RA) and synthetic retinoids exhibit potent anti-proliferative, normalization of differentiation and anti-inflammatory activities which appear to account for their therapeutic effects in acne, psoriasis, photoaging, precancerous lesions and established cancers. Although RA has shown considerable promise in dermatologic indications, certain side effects have restricted its use as a choice of agent for chronic administration. Systematic synthesis of receptor-selective retinoids has resulted in two topical drugs, Tazorac/Zorac (tazarotene) and Differin (adapalene). Tazorac is indicated for psoriasis and acne and Differin gel for the treatment of acne. These drugs bind to the retinoic acid receptor (RAR) family members. Various RAR subtype-specific and function-selective retinoids have been synthesized. These retinoids, which are in various stages of pre-clinical development for the treatment of cancers, psoriasis and as an antidote to Accutane-mediated mucocutaneous toxicity, will also be discussed in this review. Discovery of another retinoid receptor, retinoid X receptor (RXR), revealed that RXR-specific retinoids already existed in retinoid chemical libraries. Structure activity relationship studies based upon binding and transactivation assays led to the synthesis of RXR-specific ligands with high affinities for RXR subtypes. These compounds were found to be effective in the treatment of hyperglycemia in animal models of type II diabetes. The discovery of novel retinoids along with an increased understanding of the biological functions and mechanisms of action of retinoid receptors are likely to result in improved treatments for existing responsive indications and identification of new retinoid therapeutic targets.
Keywords: Pan agonists